Dampak Program Kemitraan terhadap Kelayakan Usahatani dan Pendapatan Petani Jagung di Kecamatan Sumberpucung, Jawa Timur - Hamyana, Hamyana; Cahyono, Agus; Rahmi, Ainu (Jurnal Penelitian Pertanian Tanaman Pangan, 2021)
One of the problems faced by maize farmers in Sumberpucung District, Malang, East Java, is the relatively small scale of the business, which has implications for high production costs. Efforts that can be taken to resolve these problems include a partnership pattern. This study aims to determine the feasibility of a partnership pattern and to analyze its effect on the income of maize farmers in Sumberpucung District. The research method is survey. Marginal benefit cost ratio (MBCR) analysis aims to determine the feasibility of partnership pattern farming and simple linear regression analysis is used to determine the effect of partnerships on income. The research object is the maize farmers who have partnered and who have not partnered in Sumberpucung District. The sampling technique used stratified proportional random sampling with a sample size of 76 people who were determined using the Slovin formula. The results showed that the income of partnership-patterned maize farmers was greater than that of non-partnership maize farmers with a difference of Rp. 7,573,000 / ha. Analysis of the marginal benefit cost ratio (MBCR) with a value of 9.98 (> 1) proves that the partnership pattern of maize farming is feasible to apply. This means that each additional cost of Rp. 1 will increase the benefits of farmers by 9.98. Regression analysis shows that the partnership has a significant effect on the income of maize farmers. Hypothesis testing shows the significance value of the partnership variable is 0.000 (<0.05). Thus H_1 is accepted, which means that the partnership has a significant effect on farmers’ income.